(untitled) (Journal of Industrial and Mechanical Engineering, 2023)
The United Nations adopted in 2015, 17 goals with the purpose of guiding all countries towards sustainable development, and the aspiration, to achieve them in 15 years in an action plan called "2030 Agenda". In pandemic’s time, huge changes were produced all over the world. The priorities and all global resources were focused on public health. Argentina is not the exception because this country still has a lot of issues to be solved in terms of sustainable development that were not a priority during the last periods due to the pandemic. In this context, it is relevant to study the current state of achievement of the SDGs in Argentina, in order to understand the situation of the country in compare to previous pandemic periods. It is necessary to emphasize the business sector, which is one of the sectors that most influences the achievement of these goals. This is why, the impact on the environmental performance was analysed on nationals organizations through these periods of economic detriment. The results show a wide variability in terms of stagnant goals, in retraction and a few with a slight growth that would allow achieving what was proposed. Finally, it is concluded that the work contributes to the knowledge and understanding of the current state of the SDGs and environmental management in Argentine companies.